2021
DOI: 10.1111/jvim.16112
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and histopathologic features of reversible nerve root and peripheral nerve edema secondary to disc herniation in a cat

Abstract: Nerve root enlargement with increased contrast uptake has been reported in dogs and humans secondary to nerve root compression. In cats, nerve root enlargement and contrast uptake only have been reported in association with inflammatory and neoplastic diseases, but not as a sequela to nerve root compression. An 8-year-old oriental short hair cat was presented with acute neurologic deficits consistent with left-sided sciatic nerve deficit and possible L6-S1 myelopathy. Magnetic resonance imaging (MRI) was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 66 publications
3
13
0
Order By: Relevance
“…The mean age of the cats in our study was 8.7 years, which is in agreement with the mean age of all the published feline IVDH cases thus far (8.3 years). 738 This occurrence in mature cats has been reported previously, 30,35 and is consistent with several post-mortem studies on feline intervertebral disc degeneration and herniation that found an increased occurrence of this condition in older animals. 14 When considering each type of IVDH separately, previously reported cats affected by IVDP and IVDE had a similar mean age (8.6 years), 714,16,18–23,2527,2936,38 wher...…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The mean age of the cats in our study was 8.7 years, which is in agreement with the mean age of all the published feline IVDH cases thus far (8.3 years). 738 This occurrence in mature cats has been reported previously, 30,35 and is consistent with several post-mortem studies on feline intervertebral disc degeneration and herniation that found an increased occurrence of this condition in older animals. 14 When considering each type of IVDH separately, previously reported cats affected by IVDP and IVDE had a similar mean age (8.6 years), 714,16,18–23,2527,2936,38 wher...…”
Section: Discussionsupporting
confidence: 90%
“…Only 185 cats clinically affected by IVDH have been reported in the past 50 years, most of them described from 2011 to date. 2429,3338 Moreover, several studies have separately investigated various features of each different type of IVDH, mainly as individual case reports or case series including low numbers of cats. Thus, a comprehensive overview regarding the overall clinical and MRI characteristics of this disease is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herzig et al 7 presented a case report of reversible nerve root and peripheral nerve root oedema secondary to IVDE. While this case had a foraminal component, the neurological examination was indicative of an L6–S1 localisation which, along with the severe MRI changes, is different to our presentation as this cat had obvious neurological deficits present on examination.…”
Section: Discussionmentioning
confidence: 99%